(untitled) (Journal of Political Issues, 2023)
This study describes the neutrality violations committed by the Voting Organizing Group (KPPS) in the regional head elections (Pilkada) in South Tangerang City (Tangsel) in 2020. In analyzing the phenomena that occur, the author uses the theory of election management bodies from International Democracy and Electoral Assistance (IDEA, 2015) to identify and describe various standardizations of management governance of EMBs with integrity. This study uses a qualitative method by digging up various data from print and electronic news sources and various credible sources related to the phenomenon under study. KPPS, as an ad hoc institution, has an important role in holding elections and local elections. Based on the authority possessed by the KPPS, it has become the main actor in creating election malpractice, especially what happened in the 2020 South Tangerang City Election. The findings from this research prove that the KPPS is not independent, the technical assistance provided by the KPU is not effective, it is not professional, and it is not transparent in this malpractice case. resolved regarding the substantial procedures for conducting elections